On Palestine - Chomsky, Noam. (London Penguin, 2015)
Operation Protective Edge, Israel's most recent assault on Gaza, left thousands of Palestinians dead and cleared the way for another Israeli land grab. The need to stand in solidarity with Palestinians has never been greater. Ilan Papp ǎnd Noam Chomsky, two leading voices in the struggle to liberate Palestine, discuss the road ahead for Palestinians and how the international community can pressure Israel to end its human rights abuses against the people of Palestine. On Palestine is the sequel to their acclaimed book Gaza in Crisis.
Includes index
Keywords: Palestine